1991
DOI: 10.1159/000186661
|View full text |Cite
|
Sign up to set email alerts
|

Destructive Spondyloarthropathy with β<sub>2</sub>-Microglobulin Amyloid Deposits in a Uremic Patient before Chronic Hemodialysis

Abstract: We report a case of erosive arthropathies discovered radiologically before dialysis in a uremic patient with Alport syndrome. This patient had no hereditary amyloidosis or causes of acquired generalized amyloidosis (no chronic infections or inflammatory disease, neoplasia, lymphoma or monoclonal gammapathy). Erosive spondyloar-thropathies of the cervical spine at the C5-C6 and C6-C7 levels, erosive arthropathy of the right acromioclavicular joint, metacarpal lacuna of the right hand, and lacuna of the left fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 8 publications
0
21
0
1
Order By: Relevance
“…A few case reports remain very relevant in pondering the influence of the dialysis procedure on the appearance of β 2 -microglobulin amyloidosis. They include the dialysis-related amyloidosis observed in patients mainly or exclusively treated with high-flux membranes and convective techniques [51, 52], peritoneal dialysis patients [53, 54, 55], patients before end-stage renal disease [56, 57], and 1 patient with no renal failure [58]. Although according to all these reports there seems to be insufficient evidence to think that incompatible membranes cause β 2 -microglobulin amyloidosis [59], membrane manufacturers have profusely used β 2 -microglobulin clearance as a sales argument for their respective products.…”
Section: β2-microglobulin Serum Levels In Renal Failure and Dialysis mentioning
confidence: 99%
“…A few case reports remain very relevant in pondering the influence of the dialysis procedure on the appearance of β 2 -microglobulin amyloidosis. They include the dialysis-related amyloidosis observed in patients mainly or exclusively treated with high-flux membranes and convective techniques [51, 52], peritoneal dialysis patients [53, 54, 55], patients before end-stage renal disease [56, 57], and 1 patient with no renal failure [58]. Although according to all these reports there seems to be insufficient evidence to think that incompatible membranes cause β 2 -microglobulin amyloidosis [59], membrane manufacturers have profusely used β 2 -microglobulin clearance as a sales argument for their respective products.…”
Section: β2-microglobulin Serum Levels In Renal Failure and Dialysis mentioning
confidence: 99%
“…Although the incidence of these complications appears to vary in different countries, some studies have found that ϳ33% of patients on chronic hemodialysis (CHD) develop histologically prevalent amyloidosis after 4 years of hemodialysis [dialysis-related amyloidosis (DRA)] (7 ). The histologic prevalence of ␤ 2 M amyloidosis is similar in patients in chronic peritoneal dialysis (8 ), and patients with long-standing kidney disease may develop amyloidosis in the absence of dialysis treatment (9 ). It is still unknown why ␤ 2 M becomes amyloidogenic under CHD and kidney disease conditions or why the aggregates target joints and cartilaginous tissue.…”
mentioning
confidence: 99%
“…Amyloid may occasionally infiltrate synovial structures. Amyloid arthropathy is a widely known complication of longterm hemodialysis and chronic renal failure (5,6). It is characterized by periarticular, intra-articular and intraosseous deposition of a unique form of amyloid composed of p2m icroglobulin ( 1).…”
Section: Discussionmentioning
confidence: 99%